Growth Evaluation of Native Chicken on Different Type of Hen Body Weight - Sutopo Sutopo; E. Kurnianto; Sutiyono Sutiyono; E. T. Setiatin; Y. S. Ondho; D. A. Lestari; A. Setiaji; A. Suryawijaya; D. Samsudewa (Universitas Bengkulu, 2021)
The aim of this research is to measure effect of hen body weight to the growth rate of native chicken. Ten native hens divided by two classifications (heavy and light body weight), 2 native roosters, 58 (from hen with heavy body weight) and 62 (from hen with light body weight) female day old chicks (DoC) use in this research. Hatching machine, communal cage, feeder tray, drinking jar, balance body weight and vernier calliper, were use in this research. Body weight and morphometric of female native chicken from DoC up to 10 week was measured. T-test analysis was used with help of SPSS 25. The results showed that the hen with heavy body weight resulted to the higher morphometric and body weight of female native chicken (P<0.05) on 7 and 8 week, respectively. The growth rate gain of female native chicken hatched by the hen with heavy body weight is significantly difference (P<0.05) on body weight. The conclusion is the hen with heavy body weight will result to the higher body weight and morphometric of female native chicken.